Erlang's Fixed-Point Approximation for Performance Analysis of HetNets. (21st May 2012) - Song, Guozhi; Wu, Jigang; Schormans, John; Cuthbert, Laurie
Abstract : We consider the analytic modelling of wireless systems with multiple access technologies in the perspective of teletraffic engineering and provide a framework for the performance analysis and evaluation of a wireless HetNet (heterogeneous network) system with both cellular and WLAN access technologies. In particular, an approach with Erlang's fixed-point approximation to calculate the new call blocking and handover call dropping probabilities in such systems is introduced. The model is versatile enough to cover not only cellular/WLAN HetNet systems but other wireless HetNets with difference access technologies in general.